2022
DOI: 10.1093/cercor/bhac124
|View full text |Cite
|
Sign up to set email alerts
|

The neural correlates of amplitude of low-frequency fluctuation: a multimodal resting-state MEG and fMRI–EEG study

Abstract: The amplitude of low-frequency fluctuation (ALFF) describes the regional intensity of spontaneous blood-oxygen-level-dependent signal in resting-state functional magnetic resonance imaging (fMRI). How the fMRI–ALFF relates to the amplitude in electrophysiological signals remains unclear. We here aimed to investigate the neural correlates of fMRI–ALFF by comparing the spatial difference of amplitude between the eyes-closed (EC) and eyes-open (EO) states from fMRI and magnetoencephalography (MEG), respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Prior multimodal studies performed on adults have shown that fMRI and EEG signal amplitudes are modulated by effects of aging and sex (Zhong & Chen, 2020), with the hypothesis that as vasculature reactivity declines with age, so does BOLD‐signal amplitude (Zhong & Chen, 2020). Contrarily, frequency bands of MEG‐fMRI measurements follow similar power‐law distributions with electrophysiological signals, suggesting that intensity of low‐frequency modulations stem from neural activity rather than neurovascular coupling effects (Zhang et al, 2022). Finally, a recent multimodal study enrolling a small sample of male adults to be simultaneously scanned with PET, rs‐fMRI and EEG with focus on DMN demonstrated no correlations between rs‐fMRI ReHo and fALFF metrics, FDG‐PET and EEG microstates, but revealed positive correlations between rs‐fMRI degree‐centrality metric and EEG microstates (Rajkumar et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Prior multimodal studies performed on adults have shown that fMRI and EEG signal amplitudes are modulated by effects of aging and sex (Zhong & Chen, 2020), with the hypothesis that as vasculature reactivity declines with age, so does BOLD‐signal amplitude (Zhong & Chen, 2020). Contrarily, frequency bands of MEG‐fMRI measurements follow similar power‐law distributions with electrophysiological signals, suggesting that intensity of low‐frequency modulations stem from neural activity rather than neurovascular coupling effects (Zhang et al, 2022). Finally, a recent multimodal study enrolling a small sample of male adults to be simultaneously scanned with PET, rs‐fMRI and EEG with focus on DMN demonstrated no correlations between rs‐fMRI ReHo and fALFF metrics, FDG‐PET and EEG microstates, but revealed positive correlations between rs‐fMRI degree‐centrality metric and EEG microstates (Rajkumar et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Data preprocessing was performed using the Data Processing Assistant for Resting-State fMRI (DPARSFA 2.3) toolbox . Based on blood oxygenation level-dependent signals, the ALFF was obtained to estimate local spontaneous neuronal activity . REST software was used to calculate the mALFF values and help perform statistical analysis (ANCOVA test) among the three groups (Alphasim multiple comparison correction p < 0.001 and cluster size > 100 voxels), with age, sex, and education years as covariates.…”
Section: Methodsmentioning
confidence: 99%
“… 35 Based on blood oxygenation level-dependent signals, the ALFF was obtained to estimate local spontaneous neuronal activity. 36 REST software was used to calculate the mALFF values and help perform statistical analysis (ANCOVA test) among the three groups (Alphasim multiple comparison correction p < 0.001 and cluster size > 100 voxels), with age, sex, and education years as covariates. Brain regions with significant differences in mALFF values were visualized using BrainNet Viewer software.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, brain signals measured during restingstate become essential and could help with prediction. Recent studies have shown that the eyes-closed and eyes-open resting states have distinct features based on founding from EEG and MRI measurements [16][17][18]. Moreover, the EEG features in those two states show different relationships in predicting post-stroke patient motor recovery [19][20][21].…”
Section: Introductionmentioning
confidence: 99%